Organising to meet new challenges : central banks of small countries with open financial markets - Worrell, DeLisle (ECCB BasseterreKN, 1999)
Focuses on the motivation for reorganisation, specifically to deal with the interrelation of monetary and fiscal policies, the coordination of monetary and foreign exchange operations, economic forecasting and target setting and the assessment of the health of the financial system.